Supply Chain Performance of California Papaya Commodity (Carica Papaya (L). Var Calina) - Himmatul Miftah; Riri Setyawati; Arti Yoesdiarti; Ita Novita; Tiara Amanda Lestari; Ikhsan Qodri Pramartaa (Universitas Djuanda, 2022)
The study aims to determine the marketing function, supply chain process, and supply chain performance of California Papaya suppliers to find solutions to problems that arise in the fruit commodity supply chain, namely, failure to achieve the realization of supply achievement according to recommendations. The research location at KN Jaya Farm Rancabungur Bogor Regency is from May 2022 to August 2022. Data collection methods through interviews and observations. The respondents were one-person farmers, seven suppliers, and one-person distributors. Data analysis is carried out descriptively and quantitatively analyzes supply realization compared to supply chain operation reference (SCOR) standards to determine supply chain performance achievements. Research shows the marketing functions carried out: sales and purchase activities, exchanges, physical functions: Packaging, transportation, facility functions: financing, standardization, risk protection, and market information. The supply chain process is the activity of the flow of goods, the flow of money, and the flow of information. Supply chain performance analysis consists of planning, procurement, delivery, and returns. The achievement analysis results in each matrix show that the realization of the supply chain has been carried out beyond the standards recommended by SCOR. The research concludes that the exchange function, the physical part, and the facility function carry out the marketing function. The supply chain process includes the activity of the flow of goods, money, and information. Supply chain performance has met the standard by 67% and the non-standard by 33% of the number of metrics recommended by SCOR. The recommendation of this study is to recruit suppliers from locations in the West Java region so that the metric component can 100% meet the standards and apply digital systems to ensure the efficiency and effectiveness of supply through blockchain technology.